Fatigue in offshore structural steels implications of the Department of Energy's research programme proceedings of a conference organized by the Institution of Civil Engineers, held in London on 24-25 February 1981. (Telford for the Institution, 1981)
Topics covered here include the design of the UKOSRP basic fatigue programme, the effect of North Sea service conditions on fatigue crack growth in structural steel, review of stress analysis techniques used in UKOSRP, the fatigue strength of tubular welded joints, and a summary of current design and fatigue correlation.